(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Awareness of traditional knowledge and medicinal plants can play a key role in the utilization and discovery of natural plant resources. Plants became the basis of medicine system throughout the world for thousands of years and continue to provide mankind with new remedies. Researchers generally agree that natural products from plants and other organisms have been the most consistently successful source for ideas for new drugs. The world health organization estimates that 80% of the population living in the developing countries relies exclusively on traditional medicine for their primary health care. More than half of the world’s population still relies entirely on plants for medicines, and plants supply the active ingredients of most traditional medical products. The review shows the south Indian medicinal plant products has been used by people to treat various health ailments.